1993
DOI: 10.1093/infdis/168.2.282
|View full text |Cite
|
Sign up to set email alerts
|

Protection Conferred by Neonatal Rotavirus Infection against Subsequent Rotavirus Diarrhea

Abstract: A cohort of newborns in New Delhi who were nosocomially infected with rotavirus during their first days of life were followed twice weekly for 14-23 months to determine whether neonatal infection protected them against subsequent episodes of rotavirus diarrhea. Infection occurred in 60% by the fourth day of life, was asymptomatic, and was caused predominantly by an unusual rotavirus strain (G9 P11) not previously identified in humans. The 148 children with neonatal rotavirus infection had 46% fewer attacks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
128
2
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(141 citation statements)
references
References 20 publications
7
128
2
4
Order By: Relevance
“…A baixa incidência da infecção sintomática por esse patógeno, durante os 5 primeiros meses de vida, deve-se provavelmente à presença, na mucosa intestinal, de anticorpos da classe IgA, transferidos passivamente da mãe para o filho através do leite materno, tendo em vista que a amamentação dessas crianças dura em média 3 a 4 meses. A presença desses anticorpos na mucosa intestinal das crianças nessa fase da vida parece oferecer uma certa proteção, ainda que parcial, contra a infecção por rotavírus, fazendo com que essas crianças não se infectem por esse patógeno, ou tenham a infecção na forma assintomática 2,10,18 . ApósNesse estudo, foi encontrada uma prevalência de 7,9% da infecção por rotavírus em crianças com episódio de diarréia aguda, se consideramos todas as crianças pesquisadas, abrangendo a faixa etária de 1 mês a 10 anos; e de 12,8% se considerarmos apenas as crianças da faixa etária de 1 a 24 meses de vida.…”
Section: Discussionunclassified
“…A baixa incidência da infecção sintomática por esse patógeno, durante os 5 primeiros meses de vida, deve-se provavelmente à presença, na mucosa intestinal, de anticorpos da classe IgA, transferidos passivamente da mãe para o filho através do leite materno, tendo em vista que a amamentação dessas crianças dura em média 3 a 4 meses. A presença desses anticorpos na mucosa intestinal das crianças nessa fase da vida parece oferecer uma certa proteção, ainda que parcial, contra a infecção por rotavírus, fazendo com que essas crianças não se infectem por esse patógeno, ou tenham a infecção na forma assintomática 2,10,18 . ApósNesse estudo, foi encontrada uma prevalência de 7,9% da infecção por rotavírus em crianças com episódio de diarréia aguda, se consideramos todas as crianças pesquisadas, abrangendo a faixa etária de 1 mês a 10 anos; e de 12,8% se considerarmos apenas as crianças da faixa etária de 1 a 24 meses de vida.…”
Section: Discussionunclassified
“…The [Bishop et al, 1983;Bhan et al, 1993], without the related life threatening symptoms. Large scale randomized, double blind and placebo-controlled studies for both vaccines have demonstrated high vaccine efficacy, a reduction in the rate of severe gastroenteritis episodes and no side effects [RuizPalacios et al, 2006;Vesikari et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Asymptomatic infection of newborns has also been shown to reduce the likelihood of developing severe RV-A-gastroenteritis during childhood (Bishop et al 1983, Bhan et al 1993. Surveys carried out in Mexico show that protection increases with successive reinfections and that surveyed children did not develop RV-A gastroenteritis after two RV-A infections (Velazquez et al 1996).…”
mentioning
confidence: 99%
“…Although the immune response to RV-A is not the focus of this paper, we identified multiple studies that aimed to characterize RV-A genotypes responsible for sequential RV-A infections. More specifically, we identified 12 prospective cohort surveys carried out in 10 countries (Fontayne et al 1978, Gurwith et al 1981, Bishop et al 1983, Friedman et al 1988, Georges-Courbot et al 1988, Linhares et al 1988, Reves et al 1989, Bernstein et al 1991, Bhan et al 1993, Ward & Bernstein 1994, Velázquez et al 1996, Moulton et al 1998. Altogether, these studies included 2,031 infants, aged 1-24 months, who were followed for periods varying from 12-36 months.…”
mentioning
confidence: 99%